2004
DOI: 10.1097/01.fjc.0000140209.04675.c3
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Erythropoietin Treatment for Cardioprotection in Ischemia/Reperfusion

Abstract: Erythropoietin (EPO) is a hormone known to stimulate hematopoiesis. However, recent research suggests additional properties of EPO, such as protection against ischemia/reperfusion (I/R) injury in various tissues. We studied the effect of timing of EPO administration on cardioprotection during I/R in the heart. Male Sprague-Dawley rats were subjected to 45 minutes of coronary occlusion, followed by 24 hours of reperfusion. Animals were randomized to receive saline or single dose of EPO (5,000 IU/kg) either 2 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 36 publications
10
114
2
2
Order By: Relevance
“…Cell implantation utilizing cardiac stem cells [18], embryonic stem cells [19], hematopoietic stem cells [20], MSCs [21][22][23], skeletal myoblasts [24][25][26], and cardiac myocytes (adult, fetal, or neonatal myocytes) [27,28] has been suggested to be a promising clinical approach for restoration of myocardial function after cardiac infarction. Among these various candidate cell types, MSCs have a great advantage with respect to generating functional cardiac myocytes in the infarcted myocardium because of their ease of preparation and potential to differentiate into a cardiac lineage [29,30] both in vivo and in vitro under appropriate culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cell implantation utilizing cardiac stem cells [18], embryonic stem cells [19], hematopoietic stem cells [20], MSCs [21][22][23], skeletal myoblasts [24][25][26], and cardiac myocytes (adult, fetal, or neonatal myocytes) [27,28] has been suggested to be a promising clinical approach for restoration of myocardial function after cardiac infarction. Among these various candidate cell types, MSCs have a great advantage with respect to generating functional cardiac myocytes in the infarcted myocardium because of their ease of preparation and potential to differentiate into a cardiac lineage [29,30] both in vivo and in vitro under appropriate culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is currently unknown what schedule of dosing will result in maximum tissue salvage. In a recent limited time-window study using EPO, administration at the time of cardiac reperfusion was associated with a better outcome than when given 2 h before (32). However, given the prolonged time course of ventricular remodeling and development of heart failure and its association with continued cardiomyocyte apoptosis (reviewed in refs.…”
Section: Discussionmentioning
confidence: 99%
“…EPO was found to have a beneficial effect on intestinal damage such as colitis (12), necrotizing enterocolitis, (13) and anastomosis (14) in animal models. Previous studies have shown that EPO exhibits protective effects on tissue injury associated with I/R in many tissues such as cardiac (15), kidney (16), liver (17), lung (18), brain (19), and retina (20). However, it is not known whether EPO has a protective effect in the intestinal injury associated with I/R.…”
mentioning
confidence: 99%